Yinzhihuang injection as adjuvant treatment for neonatal hyperbilirubinemia: a systematic review and meta-analysis of randomized clinical trials - Junqiang Li; Liyu Zhang; Zhongguo Chen; Min Qin (Frontiers in Pharmacology)
BackgroundNeonatal hyperbilirubinemia (NH) is a common phenomenon for neonate inpatients, and Yinzhihuang (YZH) injection is a well-known Chinese herbal formula for the treatment of NH. This study aims to evaluate the efficacy of YZH injection on NH.MethodsA comprehensive literature search was performed in four Chinese databases [China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature (CBM), China Science Journal Database (VIP), and Wan Fang ] and four English language databases (PubMed, Web of Science, EMbase and the Cochrane Library) from inception to 16 April 2024. Randomized controlled trials on YZH injection for NH were collected. Review Manager 5.4 software was used for meta-analysis and bias risk assessment.ResultTwenty-two trials involving 2,714 neonates were included. Significant differences were detected between YZH injection group and control group for total effective rate (RR = 1.15, 95%CI: 1.11 to 1.20, p < 0.00001), serum bilirubin level (the third day, MD = −36.80, 95%CI: −52.07 to −21.53; the fifth day, MD = −4.18, 95%CI: −7.50 to −0.86, p < 0.00001), and time to jaundice resolution (MD = −2.46, 95%CI -2.81 to −2.10, p < 0.00001). Adverse effects of YZH injection were described in four trials, with an incidence of 8.60%.ConclusionThe use of YZH injection as an adjuvant to NH appears to be safe and may offer superior benefits compared to routine treatment alone for NH. However, these potential benefits require confirmation in future trials employing rigorous methodology. The current evidence is not enough to recommend YZH injection as a routine treatment for NH.Systematic Review RegistrationPROSPERO (https://www.crd.york.ac.uk/prospero/), identifier, CRD42024556811.